Availability of oral antivirals against SARS-CoV-2 infection and the requirement for an ethical prescribing approach. Issue 8 (August 2022) - Dal-Ré, Rafael; Becker, Sören L; Bottieau, Emmanuel; Holm, Søren
Summary: The first two oral antivirals, molnupiravir and nirmatrelvir–ritonavir, are now becoming available in many countries. These medicines will be indicated to treat mild-to-moderate COVID-19 in non-hospitalised patients who are at high risk of progressing to severe COVID-19. These antivirals should be prescribed within 5 days of symptom onset, and after SARS-CoV-2 infection has been confirmed. However, the availability of these antivirals will be scarce for some time due to manufacturing constraints. Each country should establish a policy on the conditions under which these antivirals can be prescribed. Such a policy should be based on the fulfilment of five ethical elements: transparency, relevance, appeals, enforcement, and fairness. Following the principles of distributive justice, molnupiravir and nirmatrelvir–ritonavir should be prescribed according to a hierarchy of predicted efficacy, ideally on the basis of an evidence-based scoring system. The placebo-controlled randomised trials that supported the temporary authorisation of these two antivirals were conducted in unvaccinated patients with COVID-19, so an evidence-based prescription practice would only use these drugs for unvaccinated patients until further data become available. However, in the countries that authorised these antivirals in 2021 (the UK and the USA), both vaccinated and unvaccinated patients meeting particular requirements have access to these antivirals. Due to the complexity of prioritisation, national health authorities should start issuing their draft policies as soon as possible and these policies should be regularly updated. The effectiveness of these antivirals against the omicron variant of SARS-CoV-2 must be urgently assessed. Once implemented, molnupiravir and nirmatrelvir–ritonavir must show their effectiveness and safety in the real world, and health systems must be adequately adapted for the correct use of these antivirals.